2023
DOI: 10.1002/mren.202200075
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Extended Kinetic Model of Free‐RadicalN‐Vinylpyrrolidone Polymerization

Abstract: To predict the polymer properties produced by free‐radical polymerization of N‐vinylpyrrolidone (NVP) in aqueous solution a detailed kinetic model has been developed. The kinetic model allows to calculate the chain length distribution, the number of branching points, and the number of terminal double bonds (TDB). The latter is accounted for since TDBs are a precondition for branching. While monomer conversion can be predicted sufficiently using independently determined rate constants for propagation and termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…After the synthesis of those polyesters, structural property analysis is necessary. From our literature survey, we observed that most authors determined the molecular weight by gel permeation chromatography up to 2023. …”
Section: Features Of 25-fdca-based Homo- and Copolyestersmentioning
confidence: 99%
“…After the synthesis of those polyesters, structural property analysis is necessary. From our literature survey, we observed that most authors determined the molecular weight by gel permeation chromatography up to 2023. …”
Section: Features Of 25-fdca-based Homo- and Copolyestersmentioning
confidence: 99%